Model Laboratorium Pemasaran Ideal di Perguruan Tinggi - Rosa Prafitri Juniarti; Anik Lestari Andjarwati (Faculty of Economics, State University of Jakarta., 2018)
This research focuses on designing the fulfillment of the needs of the ideal marketing laboratory that suits the needs of industry, learning, and research. The method used is descriptive qualitative. Data are collected through literature studies, observations, and in-depth interviews with some experts in the field of marketing management, so that data can be analyzed as an ideal marketing laboratory needs. These results will impact not only on the development of science, but also make the marketing laboratory as revenue generator. The results describe the things necessary to develop an ideal marketing lab consisting of ideal facilities, marketing laboratory facilities and infrastructure, ideal marketing lab resources, and ideal laboratory marketing work program